2013
DOI: 10.1007/s10669-013-9451-8
|View full text |Cite
|
Sign up to set email alerts
|

Value of information for climate observing systems

Abstract: The Interagency Working Group Memo on the social cost of carbon is used to compute the value of information (VOI) of climate observing systems. A generic decision context is posited in which society switches from a business as usual (BAU) emissions path to a reduced emissions path upon achieving sufficient confidence that a trigger variable exceeds a stipulated critical value. Using assessments of natural variability and uncertainty of measuring instruments, it is possible to compute the time at which the requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Narrowing the uncertainty in ECS has been used in several VOI articles as an example of how improved scientific knowledge would lead to improved societal decisions and economic outcomes (Cooke et al, 2014(Cooke et al, , 2016Hope, 2014). The Cooke et al articles use a methodology shown schematically in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Narrowing the uncertainty in ECS has been used in several VOI articles as an example of how improved scientific knowledge would lead to improved societal decisions and economic outcomes (Cooke et al, 2014(Cooke et al, , 2016Hope, 2014). The Cooke et al articles use a methodology shown schematically in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis performs a Monte Carlo analysis over the full range of ECS uncertainty in IPCC (2013) report and the final VOI is the expected value over the entire ECS distribution. Cooke et al (2014) note that while the example calculation uses uncertainty in trends in one climate variable, societal decisions will clearly depend on the results of confirmation from a wide range of climate variables, so that their results should be considered as the value of an improved total climate observing system and not just one component of such a system. In that sense the VOI is the value of reaching a given level of uncertainty in climate change observations 15-20 years earlier than with less capable observing approaches.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations